2019
DOI: 10.1186/s40425-019-0745-3
|View full text |Cite
|
Sign up to set email alerts
|

Domatinostat favors the immunotherapy response by modulating the tumor immune microenvironment (TIME)

Abstract: Background: The efficacy of PD-(L)1 blockade depends on the composition of the tumor immune microenvironment (TIME) and is generally higher in tumors with pre-existing cytotoxic T cells (CTL) than in those with low CTL numbers. Nonetheless, a significant proportion of patients with pre-existing immunity fail to respond, indicating a therapeutic potential for combining PD-(L)1 blockade with additional immunomodulatory agents in both CTL-high and-low immune phenotypes. Here, we evaluated domatinostat (4SC-202), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 50 publications
7
48
0
Order By: Relevance
“…This observation explains previous reports, that Domatinostat enhances the infiltration of cytotoxic T cells into tumors of syngeneic mouse models resulting in synergistic effects when combined with immune checkpoint blocking antibodies(Hamm et al, 2018). Moreover,Bretz et al (2019), recently investigated the changes in immune gene expression signatures by RNA-seq of patient samples obtained in the SENSITIZE trial (NCT03278665). This trial evaluates the efficacy of domatinostat combined with pembrolizumab in advanced-stage melanoma patients refractory/non-responding to prior PD-1 blockade.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…This observation explains previous reports, that Domatinostat enhances the infiltration of cytotoxic T cells into tumors of syngeneic mouse models resulting in synergistic effects when combined with immune checkpoint blocking antibodies(Hamm et al, 2018). Moreover,Bretz et al (2019), recently investigated the changes in immune gene expression signatures by RNA-seq of patient samples obtained in the SENSITIZE trial (NCT03278665). This trial evaluates the efficacy of domatinostat combined with pembrolizumab in advanced-stage melanoma patients refractory/non-responding to prior PD-1 blockade.…”
supporting
confidence: 79%
“…syngeneic colorectal models, it induces infiltration of cytotoxic T cells into the tumor microenvironment and synergizes with immune checkpoint inhibitors treatment(Bretz et al, 2019). However, the relevance of the different working mechanisms of domatinostat and other HDACi are not fully understood.…”
mentioning
confidence: 99%
“…The use of the class I-selective HDAC inhibitor Domatinostat to enhance the expression of PD-1 on immune cells or PD-L1 on tumor cells and then to potentiate the efficiency of immunotherapies has been investigated by Bretz et al and has shown promising results in mice with an increase of lymphocyte infiltration and tumor regression. This study further supports the development of epigenetic therapy in combination with existing cancer immunotherapy [92]. Another study showed that the inhibition of LSD1 (histone lysine-specific demethylase) associated with an anti-PD-1 antibody suppressed tumor growth and lung metastases in breast cancer.…”
Section: Combination Of Immune Checkpoint Blockade With Epidrugssupporting
confidence: 67%
“…Omland et al successfully used 18 BCC samples to characterize important markers for cancer-associated fibroblasts and extra-cellular matrix remodeling, which were further validated experimentally (Omland et al 2017b). A recent melanoma study compared the tumor environment by Gene Set Expression Analysis in six melanoma pre-treatment and six posttreatment samples (Bretz et al 2019), which is similar in number to our vismodegib-sensitive BCC group. Second, given the in-silico nature, this study lacks histopathological validation by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 84%